Estimation of HsCRP and Cardiac Troponin I in Ischemic Heart Disease Iraqi Patients - Majida Sulaiman Aadai; Mayada Noori Iqbal; Laith Sami Mehdi; Nahlah Ghanim Abdul Majeed (Indian Journal of Forensic Medicine & Toxicology, 2021)
The present study is an attempt to investigate the changes in serum cardiac troponin (cTn) and HighsensitivityC-reactive protein (HsCRP) markers levels in Iraqi ischemic heart disease (IHD) patientsincluding stable angina (SA), unstable angina (UA) and myocardial infarction (MI) compared to the healthycontrols (HC), and to evaluate the importance of the HsCRP between these diseases combination groupsfrom the dignostic point of view, in addition to find a significant correlation between HsCRP level and someIHD risk factors. The IHD’s mortality surpass that of every major disease, so it is important that to getsuch research especially among Iraqi patients. IHD is defined as blood flow reduction to the heart muscledue to build-up of fatty strips (plaque) in the coronary arteries, it exists when the coronary blood flowbecomes incapable of both delivering sufficient oxygen (O2) to the myocardium and taking away the carbondioxide (CO2) from the cells. Collecting the blood samples from one hundred thirty IHD patients (during theperiod from October 2020 to February 2021) with ages ranged (30-80) years, of both genders, investigatedfor HsCRP by enzyme linked immune sorbent assay (ELISA) technique and cardiac Troponin (cTn I) byimmunochromography method. This study observed that the HsCRP marker is a reliable diagnostic indicatorin both MI and UA groups (but not in SA patients), and in all diseases combination groups, and that therewas significant correlations between each of the triglyceride level and the hypertension, and the HsCRPmarker level, only in the MI group, but not in SA and UA patients.